2018
DOI: 10.1016/j.copbio.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling metabolism of the human gut microbiome

Abstract: The human gut microbiome plays an important part in human health. The complexity of the microbiome makes it difficult to determine the detailed metabolic functions and cross-talk occurs between the individual species. In silico systems biology studies of the microbiome can help to identify metabolite exchanges among gut microbes. Constraint-based reconstruction and analysis methods use biochemically accurate genome-scale metabolic networks of microorganisms to simulate metabolism between species in a given mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 71 publications
0
89
0
Order By: Relevance
“…The first attempt at fully automated GEM reconstruction was made back in 2006. An algorithm, capable of curating meaningful GEMs from annotated genomes and other available information without human intervention (e.g., ModelSEED, KBase, PathwayTools), has evaded the grasp of developers . Steps towards automation have been successfully taken, with many reconstruction processes having been adopted in semi‐automatic approaches …”
Section: Metabolic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The first attempt at fully automated GEM reconstruction was made back in 2006. An algorithm, capable of curating meaningful GEMs from annotated genomes and other available information without human intervention (e.g., ModelSEED, KBase, PathwayTools), has evaded the grasp of developers . Steps towards automation have been successfully taken, with many reconstruction processes having been adopted in semi‐automatic approaches …”
Section: Metabolic Modelingmentioning
confidence: 99%
“…Second, the use of metabolic modeling serves as an efficient way to elucidate the systemic interconnected activity of all the enzymes found within and beyond the same microbial species, giving rise to a complex set of metabolic pathways . To achieve this, the constraint‐based reconstruction and analysis (COBRA) approach on genome‐scale metabolic reconstructions has been developed and applied to study the systems metabolic interactions in the human microbiota and predict the effect of their perturbations on human health caused by dysbiosis or therapeutic interventions …”
Section: Introductionmentioning
confidence: 99%
“…However, the large gamut of diversity seen in the world of microbes obviously makes the task increasingly difficult. The research on gut microbiota has progressed in terms of gene technology . It is observed that, despite having highly divergent gut microbiota composition, functional gene profiles are similar in different individuals .…”
Section: Towards a Firm Foundation – A Critical Look At The Common Grmentioning
confidence: 99%
“…Tracking of microbes, like tracking animals in zoological investigations, will help to understand such microecological forces. A molecular technique with the acronym COBRA (Constraint Based Reconstruction Analysis) enables microbial interactions with other microbes and with the host to be determined . A multitude of ecological processes governing plant‐microbe interactions provide information on how plant exudates interact with the plant microbiome .…”
Section: Towards a Firm Foundation – A Critical Look At The Common Grmentioning
confidence: 99%
See 1 more Smart Citation